Flocculation in ale brewing strains of Saccharomyces cerevisiae: re-evaluation of the role of cell surface charge and hydrophobicity - Holle, Ann Van (2018)
Flocculation is an eco-friendly process of cell separation, which has been traditionally exploited by the brewing industry. Cell surface charge (CSC), cell surface hydrophobicity (CSH) and the presence of active flocculins, during the growth of two (NCYC 1195 and NCYC 1214) ale brewing flocculent strains, belonging to the NewFlo phenotype, were examined. Ale strains, in exponential phase of growth, were not flocculent and did not present active flocculent lectins on the cell surface; in contrast, the same strains, in stationary phase of growth, were highly flocculent (>98%) and presented a hydrophobicity of approximately three to seven times higher than in exponential phase. No relationship between growth phase, flocculation and CSC was observed. For comparative purposes, a constitutively flocculent strain (S646-1B) and its isogenic non-flocculent strain (S646-8D) were also used. The treatment of ale brewing and S646-1B strains with pronase E originated a loss of flocculation and a strong reduction of CSH; S646-1B pronase E-treated cells displayed a similar CSH as the non-treated S646-8D cells. The treatment of the S646-8D strain with protease did not reduce CSH. In conclusion, the increase of CSH observed at the onset of flocculation of ale strains is a consequence of the presence of flocculins on the yeast cell surface and not the cause of yeast flocculation. CSH and CSC play a minor role in the auto-aggregation of the ale strains since the degree of flocculation is defined, primarily, by the presence of active flocculins on the yeast cell wall.